Parental childhood growth and offspring birthweight: Pooled analyses from four birth cohorts in low and middle income countries. Issue 1 (3rd September 2014) - Addo, O.Y.; Stein, A.D.; Fall, C.H.D; Gigante, D.P.; Guntupalli, A.M.; Horta, B.L.; Kuzawa, C.W.; Lee, N.; Norris, S.A.; Osmond, C.; Prabhakaran, P.; Richter, L.M.; et al.
<x xml:space="preserve">Abstract</x> Objective Associations between parental and offspring size at birth are well established, but the relative importance of parental growth at different ages as predictors of offspring birthweight is less certain. Here we model parental birthweight and postnatal conditional growth in specific age periods as predictors of offspring birthweight. Methods We analyzed data from 3, 392 adults participating in four prospective birth cohorts and 5, 506 of their offspring. Results There was no significant heterogeneity by study site or offspring sex. 1SD increase in maternal birthweight was associated with offspring birthweight increases of 102 g, 1SD in maternal length growth 0–2 year with 46 g, and 1SD in maternal height growth Mid‐childhood (MC)‐adulthood with 27 g. Maternal relative weight measures were associated with 24 g offspring birth weight increases (2 year‐ MC) and 49 g for MC‐adulthood period but not with earlier relative weight 0–2 year. For fathers, birthweight, and linear/length growth from 0–2 year were associated with increases of 57 and 56 g in offspring birthweight, respectively but not thereafter. Conclusions Maternal and paternal birthweight and growth from birth to 2 year each predict offspring birthweight. Maternal growth from MC‐adulthood, relative weight from 2‐MC and MC‐adulthood also predict offspring birthweight. These findings suggest that shared genes and/or adequate nutrition during early life for both parents may confer benefits to the next generation, and highlight the importance of maternal height and weight prior to conception. The stronger matrilineal than patrilineal relationships with offspring birth weight are consistent with the hypothesis that improving the early growth conditions of young females can improve birth outcomes in the next generation. Am. J. Hum. Biol. 27:99–105, 2015. © 2014 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc.